Analysis of School-Based Financing Management (Universitas Negeri Semarang, 2022)
This study aims to analyze the existing financing management at public junior high schools in Banjarmasin Tengah. The type of research used is a qualitative approach with a descriptive type with primary and secondary data sources taken through observation, interviews, and documentation, then the data is analyzed using the Miles and Huberman model. Technical data analysis is carried out starting from data collection, data reduction, data presentation, and drawing conclusions. To test the validity of the data, the researcher used technical triangulation and time triangulation. The resource persons in this study were BOS treasurers at SMPN 1 Banjarmasin, SMPN 2 Banjarmasin, SMPN 6 Banjarmasin, SMPN 9 Banjarmasin, SMPN 10 Banjarmasin, and SMPN 26 Banjarmasin. The results showed that; (1) Budget planning is carried out based on the principles and procedures for budgeting. The budget design used is a line item budget with the method of budgeting through a bottom -up approach. (2) Budget implementation: school funding is sourced from BOS funds which are disbursed in 3 stages a year. The use of BOS funds is in accordance with the technical guidelines for BOS funds and is carried out in accordance with the RKAS that has been prepared. However, the implementation of this budget has not been effective and efficient enough due to several obstacles. The school treasurer keeps books related to the receipt and disbursement of BOS funds. (3) Budget evaluation consists of budget oversight and accountability. Supervision is carried out by internal and external parties. Meanwhile, budget accountability is to make a report on the Letter of Accountability which is submitted through a meeting, then the report is submitted to the education office.